Improving English Reading Digital Text Skills for Multimedia Students through the Scaffolding Method - Ince Dian Aprilyani Azir; Widi Sriyanto (Universitas Cokroaminoto Palopo, 2021)
The reading process, especially in reading English texts, is a matter of extracting information from the text and a knowledge-sharing dialogue activity between readers and writers. Students admit that it is not easy to distinguish different texts that they must understand. In many cases, students often have difficulty understanding the content of the text and the context due to a lack of vocabulary and grammar. The lecturer then tried to apply several reading strategies to overcome these problems. One of them is by using the scaffolding method to help students. Then, the emergence of technology and digital sources increases the challenges of addressing the problems. Therefore, this study involved 139 students of the Multimedia Engineering Technology Study Program at the State Polytechnic of Creative Media, where the text used is mainly digital. After applying the scaffolding method, this research method uses a qualitative descriptive method describing the impact of changes on students' digital reading skills. The study carried out six types of scaffolding at three reading steps using the scaffolding method to improve students' digital text reading skills, especially students of the Multimedia Engineering Technology Study Program, which mainly use the digital text. The study results show that study result scaffolding techniques highly contribute to enhance students’ reading skills. By applying the scaffolding technique, students are able to overcome the difficulties experienced by students and get scores above the passing grade, in an average of 85, which is 20 points higher before applying such scaffolding methods in the reading activity. In addition to this, most students showed positive responses to the increasing skills and comprehension of reading the digital text through the application of the scaffolding method.